Women in politics: a case study of Iran - Shojaei, Seyedeh Nosrat; Ku Samsu, Ku Hasnita; Asayeseh, Hossien (Canadian Center of Science and Education, 2010)
Although the involvement of women in the political process as half of the world population is necessary to strengthen democracy, their place is inadequately established in active political life. At every socio-political level around the world, women found themselves as being under-represented in political decision-making. Iranian women are no exception. This paper examines women’s political participation in three different historical periods in Iran, namely the Qajar Dynasty, Pahlavi Dynasty, and the period of the Islamic Republic, to show the extent of women’s involvement in Iranian’ politicos. This paper also examines the hindering and facilitating factors that affect the political participation of women in Iran.